Frutos zoocoros con importancia para dispersores de semillas en un gradiente de degradación del bosque tropical estacionalmente seco de Zapotillo - Balcázar Bustamante, Erick Jafet (2024)
In mutualistic interactions, plant traits evolve in response to both environmental factors and dispersant agents. These adaptations include mechanisms for the dispersion of seeds by water, wind or frugivorous animals. In Zoochory, fleshy fruits have several characteristics that attract dispersants. The seasonally dry tropical forests of Zapotillos, characterized by a noticeable seasonal nature, are subject to chronic disturbances caused by overgrazing, firewood extraction and selective logging. These continuous activities, of low intensity and high frequency, cause changes in the structure and composition of plant species, transforming progressively the forest from its natural state to semi-natural, simplified, shrubby until it reaches arid land. This research evaluates the characteristics and availability of fleshy zoochorous fruits, providing key information that allows to understand the process of seed dispersal in this ecosystem. Understanding these processes is crucial for planning effective conservation and restoration strategies. We characterize the key attributes of the zoochorous fruits (such as availability, color, type of fruit, number of seeds, size and weight) in three locations: Cochas, La Manga and Limones. In order to carry out this, we set up transects of 100 by 10 m in the five forest states. We use statistical models to relate the abundance of fruits and species richness with forest conservation states. The results revealed greater variation in fruit characteristics in better preserved areas, while species with fleshy fruits showed better adaptation to degraded environments. Although no statistically significant relationship was found, we did observe relevant variations, the most conserved states showed a greater availability of fruits and richness of zoochorous species compared to the more degraded states. This highlights the relevance of zoochorous species in ecosystems that maintain resources necessary to sustain ecological interactions.